RAPD Profile Of Winged-Bean [Psophocarpus tetragonolobus (L.)DC] Mutated Using Ethyl-Methane Sulphonate - Fajri Hartanti; Adi Amurwanto; Agus Hery Susanto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Genetic diversity of winged-bean [Psophocarpus tetragonolobus (L.) DC] can be produced by induced mutation with EMS (ethyl-methane sulphonate). To identify the genetic diversity after EMS application on winged-bean, molecular analysis using RAPD (Randomly Amplified Polymorphic DNA) technique was carried out. This study aims to identify RAPD profile of winged-bean after EMS application. Winged-bean seeds of both long and short pod types were soaked in wet paper towels for 6 hours followed by soaking in EMS of 0.3% and 0.5% for 4 hours. Winged-bean seeds of both pod types without EMS served as control. Ten of the 30 primers operon technologies USA and 2 primers bangalore genei showed sufficiently clear bands (OPA 1, OPA 3, OPA 10, OPA 15, OPA 19, OPB 1, OPB 6, OPB 7, ES10C27, and ES10C28). All the ten primers produced polymorphic fragments with a total number of 320 and size ranging from 100 bp to 2,000 bp. As many as 66 loci were observed. The polymorphism values obtained ranged from 16.67% to 46.97%. This low polymorphism values indicate that EMS concentrations applied have not resulted in sufficiently high genetic variation. At the same time, the genetic distance observed were only 0.11 to 0.41.